On the acoustics of the Teatro 1763 in Bologna. (15th January 2021) - Tronchin, Lamberto; Merli, Francesca; Manfren, Massimiliano
Abstract: The need for capturing the acoustic properties and spatial information of significant ancient theatres became very important in the last years. Particularly, the knowledge of sound propagation became very important during the design or refurbishment of historic theatres and opera houses. Theatre 1763 in Villa Aldrovandi Mazzacorati, in Bologna (Italy), is chosen as a remarkable example. This is a small private theatre built by the Aldrovandi family during the 18th Century inside the historic Villa Aldrovandi Mazzacorati. The theatre maintains its original shape, indoor materials and furnishings as chairs. For this reason and its peculiarities, the theatre was deeply investigated by several architects, but no acoustic measurements were extensively conducted within the hall. This article reports the results of two measurement campaigns which were conducted in different periods and with different methodologies, to evaluate the variability of the acoustic parameters and determine intrinsic characteristics of this unique small theatre.